Dietary low ratio of n‐6/n‐3 polyunsaturated fatty acids improve type 2 diabetes mellitus via activating brown adipose tissue in male mice. Issue 3 (16th February 2021) - Yue, Hao; Liu, Wei; Zhang, Wenlong; Jia, Min; Huang, Fenghong; Du, Fangling; Xu, Tongcheng
Abstract : Abstract: The ratio n‐6/n‐3 polyunsaturated fatty acids (PUFA) has been caused widespread discussion. However, the best ratio and mechanism of n‐6/n‐3 PUFA in type 2 diabetes mellitus (T2DM) are largely unknown. This study investigated the effects of different ratio of n‐6/n‐3 PUFA diets on brown adipose tissue (BAT) and T2DM in mice. Results showed that compared with high ratio of n‐6/n‐3 PUFA (50:1) diet, lower ratio of n‐6/n‐3 PUFA (1:1 and 5:1) diets significantly increased BAT mass by 67.55% and 60.49%, decreased the fasting blood glucose (24.87% and 20.64%), total cholesterol (32.9% and 23.84%), triglyceride (33.51% and 29.62%), low‐density lipoprotein cholesterol (19.23% and 17.38%), and increased glucose tolerance by 21.99% and 15.52%. Further, qRT‐PCR analyses indicated that lower ratio of n‐6/n‐3 PUFA diets activated BAT, increased the expression of Ucp1, β‐3AR, PPAR‐γ, cAMP, GLU1, HSL, LPL, and PGC‐1α, further improved lipid and glucose metabolism in T2DM mice. In conclusion, this study substantiated that the lower ratio of n‐6/n‐3 PUFA (1:1 and 5:1) improve symptoms associated with T2DM via activating BAT. Practical Application: Dietary ratio of n‐6/n‐3 polyunsaturated fatty acids is essential for the improvement of chronic diseases. Our current study showed that 1:1 or 5:1 ratio of n‐6/n‐3 polyunsaturated fatty acids had better efficiency for type 2 diabetes mellitus via activating brown adipose tissue when compared with 1:50. This finding provided useful guidance for the daily diet of patients with diabetes.